طرائق دلالة الألفاظ على المعاني من جهة الوضوح بين علماء الحنفية وجمهور المتكلمين رحمهم الله تعالى - يوسف، إياد (جامعة الأنبار - كلية العلوم الإسلامية, 2018)
In order to determine the meaning of the word, its meaning in terms of clarity has a significant impact on the interpretation of texts, the development of judgments, and the commissioning of words and their meanings in the Islamic Shari'a. The words mentioned in the Qur'aan and Sunnah is from the verses and the hadiths of the rulings. The fundamentalists divided them on the rulings that the legislator wanted. They are divided into two parts: Section 1: Meaningful meaning. Meaning of the meaning does not require an order outside of it. Section II: vague meaning of meaning needs to understand the meaning of it to something outside of it. The words are clear, meaning that they do not need to be understood as something that is outside of them. Their levels of clarity vary in meaning. They are not one degree in the clarity of judgment, but some of them are clearer than others.
لتحديد دلالة اللفظ على معناه من ناحية الوضوح أثر ملحوظ في تفسير النصوص، واستنباط الأحكام، وقيام التكليف بمقتضى الألفاظ ومدلولاتها في الشريعة الإسلامية. والألفاظ الواردة في الكتاب والسنة من آيات وأحاديث الأحكام، قسمها الأصوليون على الأحكام التي أرادها المشرع، وهي على قسمين: القسم الأول: واضح الدلالة على معناه لا يحتاج فهم المعنى المراد منه، إلى أمر خارج عنه. القسم الثاني: مبهم الدلالة على معناه، يحتاج فهم المراد منه إلى أمر خارج عنه. والألفاظ واضحة الدلالة التي لا يحتاج فهم المراد منها إلى أمر خارج عنها، تتفاوت مراتب وضوحها في الدلالة على المعنى المراد؛ فهي ليست على درجة واحدة في وضوح الحكم، وإنما يلاحظ أن بعضها أوضح من بعض
Keywords: دلالة الألفاظ; الشريعة الإسلامية; المتكلمين; الحنفية; الفقه الإسلامى